PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS FLIPBOOK DIGITAL 'KALIFE' UNTUK MENINGKATKAN KEMAMPUAN MENULIS KALIMAT EFEKTIF - Rani Setiawaty; Setiawanda Desy Rahmawati; Arifka Aulia Wijayanti; Khoirunnisa; Windi Tri Yunita (LPPM Universitas Cipta Mandiri, 2026)
The ability to write effective sentences is an essential competency in Indonesian language learning at the elementary school level; however, field observations reveal that more than 60% of fourth-grade students still produce incoherent sentences that do not conform to standard grammatical rules. This study aimed to: (1) develop the ‘KALIFE’ (Kalimat Efektif/Effective Sentence) digital flipbook as an interactive learning medium for fourth-grade elementary school students; (2) describe the feasibility level of the media based on evaluations by material and media experts; and (3) analyze the effectiveness of the KALIFE media in improving students’ effective sentence writing skills. The study employed a Research and Development (R&D) approach using the ADDIE model with a one-group pretest-posttest design. The research subjects consisted of 15 fourth-grade students of SD NU Tanwirul Qulub, Kudus, selected through purposive sampling. Data were analyzed using a paired sample t-test and N-Gain analysis. The results showed that the mean score increased from 54.2 (pre-test) to 84.2 (post-test). The paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a statistically significant difference in students’ writing ability before and after the use of KALIFE media. The N-Gain analysis produced a mean score of 0.6598 (65.97%), categorized as moderate. It is concluded that the KALIFE digital flipbook is both feasible and effective as an interactive learning medium for teaching effective sentence writing to fourth-grade elementary school students.